Israel’s counter-terrorism policy: how effective? - Freilich, Charles D. (Terrorism and political violence, 2017)
The percentage of Israelis killed by terrorism is higher than in any other democracy. The article analyzes the threats Israel has faced, the impact terrorism has had on Israel, and the counter-terrorism policies Israel has adopted. Terrorism has had a decisive effect on Israeli elections and national security decisions, but not the economy. Israeli counter-terrorism has often been conducted without a coherent overall policy, has failed to reflect and conflicted with broader objectives, and has greatly undermined Israel's international standing. Conversely, it has enabled Israel to live in relative security and thrive, and provided its leaders with the latitude to pursue various policies, including peace, should they wish to do so.